ҚАРАҚАЛПАҚ ХАЛЫҚ АҢЫЗЛАРЫ - Алламбергенова, И.Х. (FAN va JAMIYAT, 2018)
The article deals with the Karakalpak folk tales, their differences from myths and legends and about fictional plots in folk tales.